Pedagogical Management Problem in the Pre-University Education System - Nataliya, Isaeva (2021)
Language training management is a crucial task facing teachers who carry out pedagogical activities at the pre-university training stage. The pedagogical process is a complex system involving educators and students. The article describes the result of a survey conducted to examine the role of the teacher as the educational process manager. The communicative challenges to be overcome by the teacher are detailed.